1993
DOI: 10.1038/jcbfm.1993.105
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intracellular pH in Single Rat Cortical Neurons in vitro: A Microspectrofluorometric Study

Abstract: Summary: Intracellular pH (pHi) and the mechanisms of pHi regulation in cultured rat cortical neurons were stud ied with microspectrofluorometry and the pH-sensitive fluorophore 2',7' -bis( carboxyethyl)-5 ,6-carboxyfluore scein. Steady-state pHi was 7.00 ± 0.17 (mean ± SD) and 7.09 ± 0.14 in nominally HC03 --free and HC03 -containing solutions, respectively, and was dependent on extracellular Na + and Cl -. Following an acid transient, induced by an NH] prepulse or an increase in CO2 ten sion, pHi decreased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 49 publications
(49 reference statements)
5
20
0
Order By: Relevance
“…In most of these neurons, pH i is regulated back toward normal from an acid load by Na ϩ /H ϩ exchange and from an alkaline load by Cl Ϫ / HCO 3 Ϫ exchange. This is similar to the pattern of pH i regulation found in rat cortical neurons (18). In such Fig.…”
Section: R1159 Ph I Regulation In Medullary Neuronssupporting
confidence: 69%
See 1 more Smart Citation
“…In most of these neurons, pH i is regulated back toward normal from an acid load by Na ϩ /H ϩ exchange and from an alkaline load by Cl Ϫ / HCO 3 Ϫ exchange. This is similar to the pattern of pH i regulation found in rat cortical neurons (18). In such Fig.…”
Section: R1159 Ph I Regulation In Medullary Neuronssupporting
confidence: 69%
“…We have previously shown that in response to acidification medullary neurons from all four areas studied exhibit recovery that is mediated solely by Na ϩ /H ϩ exchange, with no contribution from HCO 3 Ϫ -dependent transport (22). In most cells (19), including neurons (3,9,18,20), there is Na ϩ -independent Cl Ϫ /HCO 3 Ϫ exchange, which is believed to acidify the cell in response to an alkaline load. In agreement with these studies, we found evidence for Cl Ϫ /HCO 3 Ϫ exchange in neurons from three of the four areas that we studied (VLM, IO, and Hyp) (Figs.…”
Section: R1158mentioning
confidence: 99%
“…At normal or elevated levels of pH,, Nae-independent HCO3--ClF exchange mediates the loss of HC03-from the cell and thus acts as an acidifying mechanism (e.g. Vaughan-Jones, 1982;Boyarsky et al 1988b;Gaillard & Dupont, 1990;Ou-yang et al 1993). At low levels of pHi, however, this passive exchanger can reverse and couple the influx of HC03-to the efflux of Cl-(see Frelin et al 1988).…”
Section: Solutions and Chemicalsmentioning
confidence: 99%
“…These are the properties of an AE-like Cl À HCO À 3 exchanger. The role of the Cl À HCO À 3 exchanger under alkaline pH i conditions was first described for cardiac Purkinje fibers by Vaughan-Jones [35] and has subsequently been supported by many studies in mammalian cells [14,20,23,25,30]. Our previous work [34] functionally identified an AE-like Cl À HCO À 3 exchanger active near resting pH i and further showed a clear expression of mRNA for AE2 in these cells.…”
mentioning
confidence: 93%